Krobia petitella, a new species of cichlid fish from the Berbice River in Guyana (Teleostei: Cichlidae) - Steele, Sarah E.; Liverpool, Elford; López-Fernández, Hernán (Zootaxa, 2013)
Krobia petitella, new species, is described from the Berbice River drainage of northeastern Guyana. It is distinguished from all other described species of Krobia (K. guianensis Regan, K. itanyi Puyo and K. xinguensis Kullander) as well as the closely related ‘Aequidens’ potaroensis and ‘A’. paloemeuensis by tubed scales of the upper lateral line extending caudally into a line bisecting the lateral band blotches posterior to the mid-lateral spot. Krobia petitella n. sp. can be further diagnosed by the anterior lateral band spots lying immediately ventral to the upper lateral line, instead of being separated from the upper lateral line by a complete row of scales in all other species. Additionally, K. petitella n. sp. possesses a unique lateral coloration pattern formed by the combination of six vertical bars and four lateral band spots (vs. K. itanyi 5 bars/3 or 4 spots, K. guianensis 5/5, K. xinguensis 7/6, ‘Aequidens’ potaroensis 6/6, ‘A’. paloemeuensis 5/5). The presence of Krobia petitella n. sp. in reaches of the Berbice River drainage in the Upper Demerara–Berbice region provides a novel locality for the genus in the Guianas and suggests the Berbice River has been isolated from the rest of nearby Guianese basins, particularly the Essequibo and the Corantijn.